Nitrate-nitrogen sufficiency ranges in leaf petiole sap of Brassica oleracea L., pac choi grown with organic and conventional fertilizers - Altamimi, May Elfar; Janke, Rhonda R.; Williams, Kimberly A.; Nelson, Nathan O.; Murray, Leigh W. (My University, 2013)
Greenhouse experiments were conducted to determine the response of Brassica oleracea L., pac choi to fertilizer rates and sources and to establish optimal soluble nitrogen (N) application rates and nitrate meter sufficiency ranges. Conventional soluble fertilizer was formulated from inorganic salts with a 4:1 NO[subscript 3]-N:NH[subscript 4]-N ratio. Phosphorus (P) was held at 1.72 mm and potassium (K) at 0.83 mm for all treatment levels. The organic soluble fertilizer, fish hydrolyzate (2N–1.72P–0.83K), was diluted to provide the same N levels as with conventional treatments. Both fertilizers were applied at N rates of 0, 32, 75, 150, 225, 300, and 450 mg·Lˉ¹. Seedlings were transplanted and fertilizer application began at 18 days. Plants were harvested at 7 weeks (5 weeks post-transplanting) after receiving 15 fertilizer applications during production. Samples of the most recently matured leaves were harvested weekly and analyzed for petiole sap NO[subscript 3]-N and leaf blade total N concentration. Leaf count, leaf length, and chlorophyll content were also measured weekly. Fresh and dry weights were determined on whole shoots and roots. Optimum yield was achieved at the 150-mg·Lˉ¹ fertility rate with both conventional and organic fertilizers. Field and high tunnel experiments were conducted to validate the sufficiency ranges obtained from the greenhouse studies. Sufficiency levels of NO[subscript 3]-N for pac choi petiole sap during Weeks 2 to 3 of production were 800 to 1500 mg·Lˉ¹ and then dropped to 600 to 1000 mg·Lˉ¹ during Weeks 4 through harvest for both conventional and organic fertilizers sources. Total N in leaf tissue was less responsive to fertilizer rate effects than petiole sap NO[subscript 3]-N. Chlorophyll content was not useful in evaluating pac choi N status. These guidelines will provide farmers with information for leaf petiole sap NO[subscript 3]-N to guide in-season N applications.
Keywords: Brassica oleracea; Conventional fertilizer; Tissue total nitrogen; Organic fertilizer; Nitrate-nitrogen sufficiency